DIY academic archiving: mischievous disruptions of a new counter-movement - Karels, Martina; Hanlon, Mary; Moore, Niamh (Frontiers in Communication, 2024)
Against increasing injunctions in research governance to create open data, and knee-jerk rejections from qualitative researchers in response to such efforts, we explore a radical counter movement of academics engaged in what we term 'DIY Academic Archiving', the creation of open and accessible archives of their research materials. We turn to interviews with three DIY academic archivists, each drawing on an ethos of community archiving, as opposed to emerging open data schemes: Melissa Munn on The Gaucher/Munn Penal Press Collection (https://penalpress.com/), Eric Gonzaba's Wearing Gay History (https://wearinggayhistory.com/), and Michael Goodman's Victorian Illustrated Shakespeare Archive (https://shakespeareillustration.org/). We see these archives as engaged in a 'politics of refusal', which challenges both conventional methods and ethics in qualitative research as well as new moves towards open data. On the one hand academics are tasked to 'protect' their data by destroying it, under the guise of a supposed mode of 'care'. On the other hand, open data makes quite contrary demands, to care for data by making it 'open' for further extraction through (re)use. DIY Academic Archiving is a practice of refusal that supports a redirection away from this binary. In this article we explore how DIY academic archivists play with coding as a form of mischievous disruption, and so are contributing to new data imaginaries. We offer insight into how DIY Academic Archiving supports researchers in their theoretical, methodological and political commitments, and at the same time how it can enable researchers to take the care-full risk of archiving our research data.